El agregado racial equino en Colombia: ¿Sería el caballo Criollo Llanero Araucano el que indica mejor los ancestros? - Salamanca-Carreño, Arcesio (2024)
For three native Colombian horse breeds (Criollo Llanero Araucano, Criollo Colombiano and Paso Fino) and the Pure Spanish Breed (PRE), a total of 12 morphometric variables (weight, height at the withers, longitudinal diameter, thoracic perimeter, dorsal-sternal diameter, bicostal diameter, perimeter of the anterior cannon, height at the rump, length of the rump, width of the rump, length of the head and width of the head) were obtained for each sex from existing bibliography or from our own information. From these data, a Principal Component Analysis (PCA) was performed from the correlation matrix and then a dendrogram from the Gower distance matrix. From the results obtained in the PCA, it is concluded that PRE tends to differentiate itself from the rest by its larger size, while the Criollo Llanero Araucano differs from all of them, especially by its cephalic conformation. The dendrogram shows an isolated cluster for the PRE. The second cluster was made up of the three Colombian breeds, with the Criollo Llanero Araucano appearing as the most distant. Based on the results, it can be deduced that the horses that initially arrived in Latin America were not of big size, and that the most original characteristics (especially of the head) have been preserved in the horses from the Araucanian plains.